2019
DOI: 10.1186/s12891-019-2873-9
|View full text |Cite
|
Sign up to set email alerts
|

Charcot neuroarthropathy of the knee due to idiopathic sensory peripheral neuropathy

Abstract: Background: Charcot neuroarthropathy is a systemic disease that generates pathological changes in the musculoskeletal system, causing instability, dislocations, and deformities. Charcot neuroarthropathy of the knee, due to either diabetes mellitus or syringomyelia, is anecdotally reported with the epidemic of the diseases. However, idiopathic sensory peripheral neuropathy can inflict osteoarticular structures directly, inducing a dysfunctional Charcot neuroarthropathy. An early diagnosis and effective relief o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…One case series reported 4 patients with staphylococcus pyogenes-mediated suppurative CK, diagnosed by a leukocyte count of > 100,000 cells/mm 3 [ 18 ], and one reported presence of CPPD crystals in a patient with pseudogout-induced CK [ 13 ]. Knee deformities Valgus deformation was reported in 19 studies involving 114 patients [ 4 , 7 , 9 , 12 , 19 , 28 , 34 , 35 , 37 , 38 , 45 , 49 51 , 53 55 , 57 , 58 ] and varus deformation in 14 studies involving 34 patients [ 8 , 16 , 21 , 24 , 28 , 30 , 31 , 34 , 35 , 37 , 43 , 53 , 54 , 62 ], often presenting as instability upon valgus and varus stress tests, or a positive Bohler test [ 52 ]. Ligamentous laxity and joint hypermobility were reported in 7 studies involving 14 patients [ 7 , 19 , 22 , 26 , 32 , 50 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One case series reported 4 patients with staphylococcus pyogenes-mediated suppurative CK, diagnosed by a leukocyte count of > 100,000 cells/mm 3 [ 18 ], and one reported presence of CPPD crystals in a patient with pseudogout-induced CK [ 13 ]. Knee deformities Valgus deformation was reported in 19 studies involving 114 patients [ 4 , 7 , 9 , 12 , 19 , 28 , 34 , 35 , 37 , 38 , 45 , 49 51 , 53 55 , 57 , 58 ] and varus deformation in 14 studies involving 34 patients [ 8 , 16 , 21 , 24 , 28 , 30 , 31 , 34 , 35 , 37 , 43 , 53 , 54 , 62 ], often presenting as instability upon valgus and varus stress tests, or a positive Bohler test [ 52 ]. Ligamentous laxity and joint hypermobility were reported in 7 studies involving 14 patients [ 7 , 19 , 22 , 26 , 32 , 50 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…One patient in one case report presented with bone destruction so severe that it eroded the tibial tuberosity [ 29 ]. Neurology CK presents with characteristic neurological findings, with 29 studies involving 62 patients reporting lower limb hypoesthesia with diminished pain and temperature sensation [ 5 – 7 , 13 , 15 , 17 20 , 22 , 27 , 28 , 31 , 35 37 , 39 , 41 43 , 45 – 47 , 49 53 , 55 ], and 6 studies with one patient each reported peripheral neuropathy [ 6 , 7 , 20 , 50 , 55 , 58 ]. One patient presented with scars and burns due to lack of pain sensation [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations